Methods of Increasing the Effectiveness of Training of Athletes Engaged in Primary Training Groups - Tursunov Oqil Amrilloevich (Zien Journals, 2022)
The article gives an idea of the special tools and standards used in improving the effectiveness of training of 11-12-year-old students engaged in school athletics clubs. The also giving practical recommendations regarding the development of endurance of young athletes.
Keywords: Athletics; sports section; physical preparation; special running exercises